Pregnancy outcome and neonatal data of children born after intracytoplasmic sperm injection with a different duration of cryopreservation of spermatozoa obtained through testicular sperm extraction - Yi-Ru Tsai; Kuo-Chung Lan; Ching-Chang Tsai; Pin-Yao Lin; Fu-Tsai Kung; Yen-Chih Liu; Fu-Jen Huang (Elsevier, 2013)
Objective: To evaluate the impact of the duration of cryopreservation of testicular sperm on clinical and neonatal outcomes after intracytoplasmic sperm injection (ICSI) for patients experiencing azoospermia. Materials and methods: This study included 132 azoospermic men who participated in 212 ICSI cycles. The participating men underwent testicular biopsy for the cryopreservation of tissue to be used for subsequent ICSI cycles. The duration of the storage of testicular sperm was determined by the time of oocyte retrieval. Fertilization, embryo development in vitro, pregnancy rates, and neonatal outcomes were assessed. Results: Although the mean percentage of viability decreased from 73.2% prior to freezing to 50.2% after thawing, viable spermatozoa were visualized subsequent to thawing of the tissue samples for all patients. The potential for fertilization and subsequent embryonic development was not influenced by the duration of sperm cryopreservation up to 2 years longer. The pregnancy outcomes also varied independently of the duration of sperm cryopreservation. The duration of storage did not appear to affect the neonatal outcomes adversely, including the Apgar score and intensive care unit admission rates, although neonatal outcomes were influenced by advanced maternal age. It also has no obvious impact on the major and minor congenital malformation rate of the newborns. Conclusion: ICSI outcomes, pregnancy outcome, neonatal outcome, and congenital malformation rate appear not to be affected by the duration of the period of cryostorage. An earlier start of the ICSI cycle following the testicular sperm cryopreservation is preferable because longer preservation is associated with more advanced maternal age.